2013
DOI: 10.1039/c3ra44453h
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic system supports single mouse embryo culture leading to full-term development

Abstract: The present study demonstrates the feasibility of application of a microfluidic system for in vitro culture of preimplantation mouse embryos, with subsequent development to full-term upon embryo transfer. Specifically, embryos cultured in groups in nL volume chambers achieve pre-implantation developmental rates up to 95% (4.5 days after fertilization), while birth rates upon transfer in utero are comparable to conventional droplet culture ($30%). Importantly, while culturing single embryos in conventional micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 47 publications
4
52
0
1
Order By: Relevance
“…long-term cell culture, 15 embryo development 16 and organ-on-chip systems. In a later stage, a capping layer of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…long-term cell culture, 15 embryo development 16 and organ-on-chip systems. In a later stage, a capping layer of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Melin et al devised a microfluidic device capable of culturing a group of two embryos up to blastocyst stage in each sub‐microliter microwells . Esteves et al demonstrated that unlike clinical microdrops, single embryo cultured in a microfluidic device could successfully lead to normal birth . CFM also provides a dynamic culture microenvironment similar to in vivo conditions embryo experiences in the oviduct.…”
Section: Continuous‐flow Microfluidics In Artmentioning
confidence: 99%
“…Similarly, a microfluidic platform allowing precise nanoliter culture of mouse embryos supported embryo development to the blastocyst stage, without significant improvement, yet importantly provided ability to dissect physical requirement of single and group culture (Melin et al, 2009). Esteves et al (2013) also reported that mouse preimplantation embryos could be cultured in microfluidics and studied the impact of fluid flow, embryo density and media volume. Collectively, these experiments using mouse embryos document that microfluidics can be used for preimplantation embryo culture, they provide experimental power in precise regulation of culture environment and informative data on embryo development, and provided benefits for embryo development.…”
Section: Embryo Culture With Microfluidicsmentioning
confidence: 99%